Evaluation of domestic water measurement error: a case study - Andrés A. Mendoza (IWA Publishing, 2021)
This study presents a method to determine the operation of the measuring equipment by analyzing the metrological quality and degradation of accuracy, depending on the accumulated volume and the installation time. Different types of counters at three flow rates were tested to assess the evolution of the relative error and to determine the average error curves and rate of deterioration. The volume of apparent losses caused by the inaccuracies of the meters was also calculated. The results of the investigation establish the sub-accounting errors and the annual degradation rate were −15 and −1.88%, respectively for consumption flows below 30 L/h represented by 23% of the subscribers. For flow rates of 120 L/h, the system accounts for a 68% consumption of subscribers and an error of −1.8% and a degradation of −0.14% were recorded. Finally, for consumption flows of 1,500 L/h, the system has accounted for 9% consumption of the subscribers; over-accounting values were obtained generating an average error of 16% and a degradation of 1.68%. It is concluded that the hydrometric district has a sub-accounting error equal to −3.24%, which results in a volume of apparent losses of 1.21 m3/connection/month. HIGHLIGHT This paper proposes a methodology that allows determining the operation of the domestic water meter by analyzing the metrological quality and degradation of accuracy, specifically by the statistical calculation of the weighted measurement error, the annual degradation and the volume of apparent losses of the domiciliary meters installed in urban areas, using a hydraulic bench test.;